Treatment of Intermittent Claudication with Mesoglycan – A Placebo-controlled, Double-blind Study - Nenci, Giuseppe G.; Gresele, Paolo; Ferrari, Gianni; Santoro, Luigi; Gianese, Francesco; for the Mesoglycan Intermittent Claudication Group (Thrombosis and Haemostasis, 2001)
Objective: To assess the effect of treatment with mesoglycan, a sulphated polysaccharide compound, on the walking capacity of patients with stage II peripheral arterial disease. Methods: Non-diabetic out-patients with intermittent claudication, duplex ultrasound evidence of peripheral atherosclerosis, ankle/arm index <0.80, systolic ankle pressure >50 mmHg, and absolute walking distance (AWD) between 100 and 300 m (standardised treadmill test) were eligible. After a 5-week run-in on single-blind placebo, patients were randomised to double-blind treatment with mesoglycan, 30 mg/day intramuscularly for 3 weeks followed by 100 mg/day orally for 20 weeks, or matching placebo. All patients received low-dose aspirin and lifestyle instructions. Clinical response was defined as an AWD increase at Week 23 >50% over baseline. Health-related quality of life and ischaemic events were assessed as secondary efficacy variables. Results: 242 patients were randomised and 237 were assessed for clinical response. Patients achieving clinical response were 59/118 with mesoglycan (50.0%) and 31/119 with placebo (26.1%; p <0.001). Geometric mean AWD increased from 192 to 298 m with mesoglycan, and from 192 to 238 m with placebo (p <0.001). Pain-free walking distance showed a non-significant increase with mesoglycan (p = 0.057). Changes in quality of life scores were in favour of mesoglycan. The rate of ischaemic events was 1/120 on mesoglycan and 6/122 on placebo (p = 0.053). The rate of non-ischaemic adverse events leading to treatment discontinuation was 7/120 and 4/122, respectively. Conclusion: Treatment with mesoglycan improves the walking capacity of patients with intermittent claudication, and might confer additional antithrombotic protection over that of aspirin.
Keywords: Peripheral arterial disease; intermittent claudication; treadmill test; mesoglycan; randomised clinical trial